The Emergence of Novel Sequence Type Strains Reveals an Evolutionary Process of Intraspecies Clone Shifting in ICU-Spreading Carbapenem-Resistant Klebsiella pneumoniae - Zhao, Dongdong; Shi, Qiucheng; Hu, Dandan; Fang, Li; Mao, Yihan; Lan, Peng; Han, Xinhong; Zhang, Ping; Hu, Huangdu; Wang, Yanfei; Quan, Jingjing; Yu, Yunsong; et al. (Frontiers in Microbiology, 2021)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) is an urgent public health problem worldwide, and its rapid evolution in the clinical environment has been a major concern. A total of 99 CRKP isolates spreading in the ICU setting were included and subjected to whole-genome sequencing, and their sequence types (STs), serotype loci, and virulence determinants were screened based on genome data. The phylogenetic structure was reconstructed based on the core genome multilocus sequence typing (cgMLST) method. Regions of recombination were assessed. Biofilm formation, serum resistance assays and a Galleria mellonella infection model were employed to evaluate strain virulence. A novel ST, designated ST4496, emerged in the ICU and spread for 6 months before its disappearance. ST4496 was closely related to ST11, with only a single-allele variant, and ST11 is the most dominant clinical clone in China. Recombination events occurred at capsule biosynthesis loci and divided the strains of ST11 and its derivative ST4496 into three clusters, including ST11-KL47, ST11-KL64 and ST4496-KL47. The phylogenetic structure indicated that ST11-KL47 was probably the origin of ST11-related strain evolution and presented more diversity in terms of both sequence similarity and phenotypes. ST4496-KL47 cluster strains presented less virulence than ST11-KL64, which was probably one of the factors preventing the former from spreading widely. In conclusion, ST4496-KL47 was probably derived from ST11-KL47 via intraspecies shifting but was less competitive than ST11-KL64, which also evolved from ST11-KL47 and developed increased virulence via capsule biosynthesis locus recombination. ST11-KL64 has the potential to be the predominant CRKP clone in China.